Featured risk evaluation of nautical navigational environment using a risk cloud model. Issue 3 (1st September 2020) - Tian, Yan-Fei; Chen, Li-Jia; Huang, Li-Wen; Mou, Jun-Min
Abstract : In this paper, a risk cloud model (RCM) based on cloud model theory is proposed for evaluating risks in the nautical navigational environment (NNEt). To validate the method, the proposed strategy is applied to a risk evaluation of NNEt of the waters around the Hangzhou Bay Sea-Crossing Bridge and the results are compared with those of a conventional fuzzy theory-based evaluation approach. The results show that risk evaluations based on the proposed RCM are robust, can accommodate uncertainty, can leverage multi-channel information, and provide a full-featured analysis of NNEt. In addition, plots of the RCM droplets provide an intuitive depiction of the risk level, which is extremely beneficial in analyses of the results. Thus, the proposed RCM and implementation method is well-suited for use in conducting risk evaluation of NNEt.